EFFECTS OF IMPORTS OF MAIN AND PROCESSED RAW MATERIALS FOR THE FOODS AND BEVERAGES INDUSTRY ON ECONOMIC GROWTH IN INDONESIA - Lusi Dyana Hasra; Cut Putri Mellita Sari (Journal of Malikussaleh Public Economics, 2019)
The purpose of this study is to analyze the relationship between Imports of Main Raw Materials and Processed Materials for Industry to Indonesian Economic Growth. This study uses secondary data in the year 1997-2015 obtained from BPS (Central Bureau of Statistics) Indonesia. Data are analyzed using Vector Autoregression (VAR) with Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD). The results of the study indicated that there were Co-interrelations of each variable to the variable itself and other variables. Variable Imports of Primary Raw Materials had the most effective effect in the short run on Economic Growth, while the variable Imports of Processed Raw Materials had the most effective effect in the long run on Economic Growth.